2020
DOI: 10.1002/qua.26417
|View full text |Cite
|
Sign up to set email alerts
|

Half‐metallicity, magnetism, mechanical, thermal, and phonon properties of FeCrTe and FeCrSe half‐Heusler alloys under pressure

Abstract: The half-metallicity of Heusler alloys is quite sensitive to high pressure and disorder. To understand this phenomenon better, we systematically studied the half-metallic nature, magnetism, phonon, and thermomechanical properties of FeCrTe and FeCrSe Heusler alloys under high pressure using ab initio calculations based on density functional theory. The ground-state lattice constants for FeCrTe and FeCrSe alloys are 5.93 and 5.57 Å, respectively, consistent with available theoretical results. Formation energy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This is in accordance with previous studies reported in the literature. [59][60][61] . The results are found to be significantly different for both the phases.…”
Section: Iii13 Electronic and Magnetic Propertiesmentioning
confidence: 99%
“…This is in accordance with previous studies reported in the literature. [59][60][61] . The results are found to be significantly different for both the phases.…”
Section: Iii13 Electronic and Magnetic Propertiesmentioning
confidence: 99%
“…Depending upon the stoichiometry, Heusler alloys are divided into three categories: (i) equiatomic half-Heusler (XYZ), [12][13][14][15][16][17][18][19][20][21][22] (ii) 2:1:1 full-Heusler (X 2 YZ) [23][24][25][26][27][28][29] and (iii) equiatomic quaternary Heusler (XX YZ), in which X, X , Y are transition-metal (TM) elements and Z is the main group sp elements. [30][31][32][33][34][35][36][37][38][39][40] The equiatomic quaternary Heusler (EQH) alloys can be obtained by replacing one TM element X to another TM element X in the full-Heusler alloy X 2 YZ.…”
Section: Introductionmentioning
confidence: 99%